Prevalence of Associated Factors of Depressive Symptoms among School Going Children’s - Sonal B. Dhobe1 , Samruddhi Gujar2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Depression is the most often encountered in the world of mental illness. In adulthood these mental disordersdo not understand as people do not want to share their mental illness with health care providers, they arefearful of receiving approval from the physician. The community people in the last century did not accept theexistence of mental illness to the children. Nowadays some studies can provide evidence of mental illnessand treatment, or the medical field is also evolving so that people believe disease and death rates. Earlierstudies show that depression is prevalent in adolescents (10% to 60%). The mood disorder (depressivemood) may inform lows all around, people may go to sadness in this condition, and in a severe case, peoplemay end their lives. A person may suffer for a long period in a situation in which he or she feels sad anddoes not participate in social, personal, professional life. In all life situations, the person feels low and doesnot feel pleasure in everyday life, so if the individual can feel these things in their life so that they considerdepression. 3 influence of depression mood which is unusual at a particular age. This can lead to negativeeffects on a friend, social, and family relationship. 4 most suicide and suicidal behavior can lead to majordepressive disorders. Younger depression can lead to chronic waxing and increased risk of major depressionin adulthood. Some studies can indicate that depression may occur early in adulthood as opposed to people’spast lives.